A comparison of the biomechanical stability of pedicle-lengthening screws and traditional pedicle screws: an in vitro instant and fatigue-resistant pull-out test. (April 2018) - Qian, L.; Jiang, C.; Sun, P.; Xu, D.; Wang, Y.; Fu, M.; Zhong, S.; Ouyang, J.
Abstract : Aims: The aim of this study was to compare the peak pull-out force (PPF) of pedicle-lengthening screws (PLS) and traditional pedicle screws (TPS) using instant and cyclic fatigue testing. Materials and Methods: A total of 60 lumbar vertebrae were divided into six groups: PLS submitted to instant pull-out and fatigue-resistance testing (groups A1 and A2, respectively), TPS submitted to instant pull-out and fatigue-resistance testing (groups B1 and B2, respectively) and PLS augmented with 2 ml polymethylmethacrylate, submitted to instant pull-out and fatigue-resistance testing (groups C1 and C2, respectively). The PPF and normalized PPF (PPFn) for bone mineral density (BMD) were compared within and between all groups. Results: In all groups, BMD was significantly correlated with PPF (r = 0.83, p < 0.001). The PPFn in A1 was significantly less than in B1 (p = 0.006) and C1 (p = 0.002). The PPFn of A2 was significantly less than in B2 (p < 0.001) and C2 (p < 0.001). The PPFn in A1, B1, and C1 was significantly greater than in A2 (p = 0.002), B2 (p = 0.027), and C2 (p = 0.003). There were no significant differences in PPFn between B1 and C1, or between B2 and C2. Conclusion: Pedicle lengthening screws with cement augmentation can provide the same fixation stability as traditional pedicle screws and may be a viable clinical option. Cite this article: Bone Joint J 2018;100-B:516–21.